2019
DOI: 10.3390/ijerph16224535
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Trend in Attendance for Breast Cancer Screening in Lithuania, 2006–2014

Abstract: In Lithuania, a Nationwide Breast Cancer (BC) Screening Program was launched in 2005, offering mammography for women aged 50 to 69 years, every other year. This study aimed to determine the trend in the attendance for mammography screening during 2006–2014 and to identify the factors that are predictive for participation in it. The study sample consisted of 1941 women aged 50–64 years, who participated in five cross-sectional biennial postal surveys of Lithuanian Health Behavior Monitoring, carried out in inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
1
8
0
1
Order By: Relevance
“…Current or previous smoking status was associated with a lower IRR of attendance, which is in line with previous studies, 12,26 implying that smoking could be a habit attributable to women less concerned about breast cancer prevention compared to non-smokers, who are possibly more aware of the positive sides of a healthy lifestyle. PA ≥2 h a week was associated with a higher IRR of attendance in the program.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Current or previous smoking status was associated with a lower IRR of attendance, which is in line with previous studies, 12,26 implying that smoking could be a habit attributable to women less concerned about breast cancer prevention compared to non-smokers, who are possibly more aware of the positive sides of a healthy lifestyle. PA ≥2 h a week was associated with a higher IRR of attendance in the program.…”
Section: Discussionsupporting
confidence: 91%
“…Both higher and lower education levels have been reported to be negatively associated with screening attendance. 12,24,26 Our results suggest that women with college/university education attend less frequently compared to women with a lower level of education. However, the differences are very small, and the statistical significance could mainly have been achieved due to the large sample size.…”
Section: Discussionmentioning
confidence: 59%
“…Our results also showed that weekly exercise was positively associated with screening attendance. Health attitudes may be the reason for participating in screening ( 31 ). Jin et al ( 32 ) indicated that women who underwent regular medical checkups were more likely to be screened.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also showed these results. In addition to health attitudes ( 31 ) and communication with healthcare staff ( 32 ), a possible reason is that the project for “two-cancer” screening may be included in some health checkups. Thus, it is important to promote women's attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation